Multicolor flow cytometric assessment of Ki67 expression and its diagnostic value in mature B-cell neoplasms - Mao, Xia; Li, Yi; Liu, Songya; He, Cheng; Yi, Shujuan; Kuang, Dong; Xiao, Min; Zhu, Li; Wang, Chunyan (Frontiers in Oncology, 2023)
Background: There is no unified standard data about the sensitivity and specificity regarding flow cytometry analysis of Ki67 expression during lymphoma diagnoses. Objective: This evaluated the efficacy of multicolor flow cytometry (MFC) in an estimate of the proliferative activity of B-cell non-Hodgkin lymphoma by comparing the expression of Ki67 using MFC and immunohistochemicals (IHC). Method: A total of 559 patients with non-Hodgkin B-cell lymphoma were immunophenotyped using sensitive MFC, of which 517 were newly diagnosed and 42 were transformed lymphomas. Test samples include peripheral blood, bone marrow, various body fluids, and tissues. Through MFC multi-marker accurate gating, abnormal mature B lymphocytes with restricted expression of the light chain were screened. Ki67 was added to determine the proliferation index; the positive rate of Ki67 in tumor B cells was evaluated by cell grouping and internal control. For tissue specimens, MFC and IHC analyses were performed simultaneously to assess the Ki67 proliferation index. Results: The positive rate of Ki67 by MFC was correlated with the subtype and aggressiveness of B-cell lymphoma. Ki67 could distinguish indolent lymphomas from aggressive subtypes with a cut-off value of 21.25%, and differentiate transformation from indolent lymphoma with a cut-off value of 7.65%. The expression of Ki67 by MFC (regardless of the type of samples)was highly agreement with the Ki67 proliferative index of tissue samples assessed by pathologic immunohistochemistry. MFC showed a fairly constant negative bias in evaluating tissue or bone marrow samples, compared with IHC. Conclusions: Ki67 is a valuable flow marker that can distinguish between indolent and aggressive types of lymphoma and assess whether indolent lymphomas are transformed. Using MFC to evaluate the positive rate of Ki67 is important in clinical settings. MFC has unique advantages in judging the aggressiveness of lymphoma in samples of bone marrow, peripheral blood, pleural and ascites, and cerebrospinal fluid. This is particularly important when tissue samples cannot be obtained, making it an important supplement for pathologic examination.